Application of the Map-Q Learning Model to Improve Student Activities and Learning Outcomes in Geography Subjects - Harby Prasetya; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2020)
Tigo Lurah sub-district is one of the sub-districts in Solok Regency. This sub-district is the most underdeveloped sub-district among other sub-districts in Solok Regency. Some of the reasons why Kec. Tigo Lurah left behind can be seen from the access road, road network, and internet network. These things also have an impact on the education process in Tigo Lurah, especially SMA 1 Tigo Lurah. SMA 1 Tigo Lurah is the only small school in the Tigo Lurah area. This school is supported by four SMA and one MTSS. Although supported by these five schools, less than 70 students are studying at SMA 1 Tigo Lurah. This happens because of the large number of students who study in Vocational Schools and Madrasah in Solok City. SMA 1 Tigo Lurah only has students from two villages, namely Nagari Batu bajanjang and Nagari Rangkiang Luluih. The distance factor is the main thing that makes three Nagari such as Garabak Data, Smanau, and Sumiso reluctant to attend SMA 1 Tigo Lurah. In addition to the problem of the lack of interest in students to study at SMA 1 Tigo Lurah. Schools also face opposition from students who lack learning activities and learning outcomes. The majority of these students only follow the learning process just to play (fill spare time) and there is no motivation to learn. To overcome this problem the author uses a learning model that the author designed himself, namely Map-Q Based on the results of research conducted by the author, it can be concluded that: a. Learning activities using the map-Q model have increased by 16.3% while learning outcomes have increased by 28.3%.